PERBEDAAN LATAR BELAKANG KELUARGA MAHASISWA JURUSAN PENDIDIKAN SENI RUPA UNNES DAN HUBUNGANNYA DENGAN MINAT PPL - U, Kamsidjo B (Universitas Negeri Semarang, 2009)
The research is about the students family background in its relation to theirwillingness to join PPL. The respondents were twenty seven 5 semester students ofArts Education Department of Faculty of Languages and Arts of Semarang StateUniversity. There were 15 students who were from teacher family. Three of thestudents (20%) falls under high category, while 12 of them (80%) falls under moderatecategory. There were 12 students who came from non teacher family background.From the 12 students, 3 of them (25%) fell under high interest category, 6 of them(50%) fell under moderate interest category. One student (8.2%) fell under insufficientcategory. Two students (16.3%) fell under low category. In essence 22.22% studentsfell under high interest category, 66.66% moderate interest category, and 3.7%insufficient category, and 7.4% low category. Normative, empirical analysis, and evenpercentage description showed that the interset of the students, both from the teacherand non teacher family fall under moderate category. There was not significantdifference between students who were from teacher families and those who were fromnon teachers family. Psychologically, the students were natural. This means that theinternal factor of the students played a greater role compared to their external factors.thKata kunci : keluarga, mahasiswa, dan minat PPL